Sanksi Pidana Kerja Sosial Terhadap Tindak Pidana Ringan Sebagai Upaya Pembaharuan Hukum Pidana Nasional - Slat, Teafani Kaunang (Universitas Negeri Malang, 2019)
This study aims to evaluate the provisions related to social service crime in the draft criminal law (R-KUHP) in the act of national criminal law reform. The study uses a normative juridical with a statue approach. The urgency of social service as the main criminal sanction against minor offenses can be justified through a combined criminal theory. Social service appropriate in the case of minor criminal offenses because this criminal has the advantage, i.e., the criminal sanction is punitive and still maintaining that the perpetrator can reintegrate into the community. The provisions of social service in the R-KUHP are quite complete and comprehensive. But several things can be noted, i.e., the need for adjustments to several clauses in the R-KUHP related to the provisions of social service and assessment to test the defendant’s readiness to work in the community needs to be more oriented towards community safety.